Calcium carbonate production by the massive coral Mussismilia hispida in subtropical reefs of the Southwestern Atlantic - Oliveira, L.S.; Sanches, Fábio H.C.; Silva, M.A.; Longo, P.A.S.; Laurino, Ivan R.A.; Motta, Fabio dos Santos; Pereira-Filho, Guilherme H. (Marine environmental research, 2025)
Corals, as primary calcifiers, play a vital role in synthesizing calcium carbonate (CaCO3) to build their skeletons, contributing to the formation of complex benthic habitats that support high biodiversity and marine productivity. However, coral habitats have dramatically declined worldwide due to ocean warming and acidification. Interestingly, the subtropical Southwestern Atlantic (SWA) has emerged as a potential refuge, where corals like Mussismilia hispida exhibit resilience to thermal anomalies. In this study, we estimate CaCO3 production by M. hispida in subtropical SWA reefs, revealing an average growth rate of 4.3 ± 1 mm/year and a CaCO3 production rate of 1.31 ± 0.3 kg. m−2. year−1. These values are comparable to tropical reef systems, suggesting that M. hispida contributes significantly to carbonate production, even in higher latitude environments. Moreover, despite experiencing one of the most intense thermal anomalies recorded, colony abundance (i.e., ind. m−2) and carbonate production remained stable, emphasizing the potential of the region as a climate refuge. While many tropical reefs act as net CO2 sources due to the release of CO2 during calcification, SWA subtropical reefs present lower coverage of corals. They are dominated by algae and other primary producers, acting as an important potential carbon sink through photosynthesis and long-term storage of carbon over centuries as mineralized CaCO3. Thus, we provide evidence that M. hispida, by producing ∼170 tons. year−1 of CaCO3 in the subtropical reefs of the Alcatrazes Archipelago, acts as a key player in carbon sequestration and CaCO3 production in higher latitude SWA areas. •Subtropical Mussismilia hispida rivals tropical reefs in CaCO3 production.•CaCO3 production remains stable despite extreme thermal anomalies.•Alcatrazes Archipelago act as carbon sinks, with ∼170 tons/year of CaCO3.